Pencegahan Stunting Melalui Pemberdayaan Ibu Hamil dengan Pendekatan Holistik: Mencapai Generasi yang Sehat dan Berkualitas - Delima; Herwati; Metri Lidya; Erwani; Elsyie Yuniarti; Asep Irfan (CV. CENDIKIA JENIUS INDONESIA, 2026)
This community service program aimed to prevent stunting through the holistic empowerment of pregnant women in the working area of Belimbing Public Health Center, Kuranji District, Padang City. The implementation method employed a participatory and cross-sectoral collaborative approach, beginning with a Community Deliberation Meeting (Musyawarah Masyarakat Kelurahan), followed by the establishment of Pregnant Women Classes, maternal health assessments (antenatal care, nutritional status, and hemoglobin examination), provision of iron tablets and supplementary food, as well as refresher training and capacity strengthening for health cadres. The results demonstrated a significant improvement in pregnant women’s knowledge regarding stunting prevention, increasing from 55.3% to 92%, an increase in antenatal care participation up to 98%, a reduction in the prevalence of anemia among pregnant women from 17.69% to approximately 4–5%, and a decrease in chronic energy deficiency from 5.06% to 2.1%. In addition, the knowledge level of health cadres improved substantially after training. In conclusion, the holistic empowerment of pregnant women integrated with the active involvement of cadres, families, and cross-sectoral support is effective in improving maternal health status and reducing stunting risk factors from the prenatal period.